Insta-Poetry as a Popular Product: A Case Study on Rupi Kaur Milk & Honey - Aspany, Nur Fitriyanti; Lutviani Murni, Siti Nurlaeli (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2024)
In 2014, Rupi Kaur published Milk & Honey, a collection of poetry and prose exploring the female experience that originally appeared on social media, to widespread success. Insta-poetry, poetry disseminated through the social media platform Instagram, has since become a highly popular modern literary form, continuing to gain popularity since the day it was first published in book form. This research examined the phenomenon of Insta-poetry as a popular product with a case study of Milk & Honey, exploring the reasons Kaur's first self-published work was so popular and the contestations that drove Milk & Honey to become a popular Insta-poetry product. Foucault’s subject-power theory and Aeron Davis’ production were employed to retrieve the findings. Furthermore, a descriptive-qualitative method was applied in conducting and analyzing the data. It was found that Kaur utilized Insta-poetry to challenge social norms and empower women, trauma, and relationships. Consequently, Kaur decided to self-publish her Insta-poetry in a book even though it was considered too basic and detracted from the complexity of traditional poetry. Regardless of the controversy, Kaur has been able to play an impactful position in introducing poetry to a new generation and modernizing the way literature is disseminated.